Test 8 × 32.8 m as a diagnostic and fitness level control indicator in basketball (Diagnostic test in basketball) - Przybylski, S.; Makar, P.; Bielec, G. (Baltic Journal of Health and Physical Activity, 2012)
Physiological studies conducted for over 20 years on basketball players have shown an increasing share of anaerobic efforts during the game. The players` throw effectiveness and their ability to move quickly on the playing field often determine the result of the match. The current control of kinematics and biochemical variables is crucial in the modern training process. The study was conducted on an 11-person group of male athletes from a Polish first-league basketball team. The subjects had to perform a fitness test proposed by the authors: 8x32.8m with bouncing, throwing a ball to the basket and running back without the ball. The course of the test was video-recorded. A blood sample was taken in the 1st, 3rd, 13th and 23rd minute after the test. The level of lactic acid as well as glucose concentration were assessed by Lactate Scout and FreeStyle Lite apparatus. The study revealed individual differences in the level of special fitness among the players. The throw effectiveness varied from 37 to 75% (mean 59%), while the maximal lactic acid concentration varied from 6.3 to 8.5 mmol/l (mean 7.2 mmol/l). The average maximal glucose concentration was 124.6 mg/dl. The range of lactic acid restitution time differentiated the players from 21 to 55 minutes (mean 30min). Application of the test in practice allows determining the basic values of kinematic techniques of basketball players in terms of biochemical changes. It should be an effective tool to control and optimize the basketball training process.